The Palgrave handbook of violence in Africa - Mlambo, Obert B.; Chitando, Ezra (Palgrave Macmillan, 2024)
Foreword by Professor Stathis Kalyvas, Oxford -- SECTION A: Technologies of Violence in Africa -- 1. Systemic and Epistemic Violence in Africa; Patricia Pinky Ndlovu: Chair of Sociology and Sabelo J. Ndlovu-Gatsheni, Professor and Chair of Epistemologies of the Global South with Emphasis on Africa and Vice-Dean of Research in the “Africa Multiple Cluster of Excellence” -- 2. Theoretical underpinnings of violence in Africa; Clive Tendai Zimunya: Lecturer of Philosophy and Obert Bernard Mlambo, Associate Professor of Classical Studies and History -- 3. Technologies of Violence in Africa; Obert Bernard Mlambo, Associate Professor of Classical Studies and History and Wesley Mwatwara, Historian -- 4. Of Exile as Violence in Lewis Nkosi’s Thought; Tendayi Sithole, Department of Political Sciences -- 5. Africa and violence: the metamorphosis and the participation of Child soldiers in conflict zones; Toyin Cotties Adetiba, Department of Political and International Studies -- 6. Structural violence and resource curse in Angola -- 7. Violence against nature in Africa: a historical assessment; Marlino Eugénio Mubai, History, Environmental and Political Ecology -- SECTION B: The State and Violence in Africa -- 8. Understanding Electoral Violence in Africa; Matlosa Khabele, African Union Commission Director for Political Affairs -- 9. Understanding violence from an interpersonal perspective: The case of Zimbabwe and state sponsored violence; Chenai G. Matshaka, Centre for Mediation in Africa and Ruth Murambadoro, the Centre for Feminist Research -- 10. ‘Dirge to Slit Bodies’: EndSARS, Police Brutality and Nigerian Dystopia in Jumoke Verissimo and James Yéku’s Soro Soke: When Poetry Speaks Up; Ayokunmi O. Ojebode, the Institute for Name-Studies (INS) -- 11. The Silent Violence in Africa- Manifestations of Political Violence; Annie Barbara Chikwanha, Politics and International Relations -- 12. Beyond ethnicity: Reflections on the history and politics of violence in Uganda; Evarist Ngabirano, the Makerere Institute of Social Research (MISR) -- 13. Ungoverned Space and National Security in Nigeria; Arinze Ngwube, Department of Political Science -- 14. Bound to violence? Interrogating violence in Francophone African literatures; G. Ncube, Stellenbosch University -- SECTION C: Children, Youth and Violence -- 15. Child Soldiers, Conflict and Cultures of Violence in Contemporary Africa, c.1980-2000s; Stacey Hynd, African History and Co-Director of the Centre for Imperial & Global History -- 16. Youth, Proliferation of Small Arms and Light Weapons and Conflicts in 21st Century Africa; Babayo Sule, Department of Political Science and Ibrahim Kawuley, Department of Political Science -- 17. Youth, Violence and Political Accumulation: Urban militias in Harare; Simbarashe Gukurume, Sociology and Social Anthropology and Godfrey Maringira, Sol Plaatje University -- 18. “Even the Holy Book Recommends it”? Corporal Punishment, the Bible and Sacred Violence in Southern Africa; Ezra Chitando, Phenomenology and History of Religion -- 19. “Even the Holy Book Recommends it”? Corporal Punishment, the Bible and Sacred Violence in Southern Africa; Ezra Chitando, Phenomenology and History of Religion -- SECTION D: Violence, Memory and the Law in Africa -- 20. Discourses on Political Violence and State Legitimation in Official Commissions of Inquiry in Africa; Claire-Anne Lester, Stellenbosch University (Legal Sociology, Political Transitions, Transitional Justice); 21. Remembrance as a confrontation of violence? A religio-ethical consideration of the role of memory in a Zimbabwe established and ruled by violence; Collium Banda, Theology; 22. Geographies of Violence and Informalization: The Case of Mathare Slums in Nairobi, Kenya; Maurice Omollo, Maasai Mara Universit and Solomon Waliaula, Maasai Mara University -- 23. Piracy and Violence off the Coast of Nigeria: A Theoretical Analysis; Kalu Kingsley, the Cultural Heritage Preservation Research Institute -- 24. Incest as Dismissal: Anthropology and Clinics of Silence; Parfait D. Akana, Sociologist & Anthropologist -- 25. Violence and post-coloniality in contemporary Zimbabwean literature: the works of Chenjerai Hove; Oliver Nyambi, University of the Free State -- SECTION E: Religion and Cultural Violence in Africa -- 26. In God’s Name: Drivers of Violent Extremism in the Northeast Nigeria; Jacinta Chiamaka Nwaka, Peace and Conflict History -- 27. The Epistemic Scaffolding of Religious Violence; Kizito Kiyimba, SJ -- 28. Life transforming Intercultural Pastoral Care and Counseling with transgender and intersex communities in Botswana; Tshenolo Madigele: Theology Lecturer and Oabona Sepora: Institute of Development Management -IDM -- 29. Enchanted Worldviews and Violence Against Persons with Albinism in Sub-Saharan Africa; Francis Benyah, The Study of Religions -- 30. Violence against persons with albinism in Malawi; Jones Hamburu Mawerenga, Systematic Theology, Christian Ethics, and African Theology -- SECTION F: Gender and Violence in Africa; 31. Sexual Violence Against Girls and Women in African Conflict; Veronica Fynn Bruey, Legal Studies -- 32. Persisting inequalities: An intersectional view of climate change, gender and violence; Mary Nyasimi, Inclusive Climate Change Adaptation for a Sustainable Africa and Veronica Nonhlanhla Jakarasi -- 33. Violence against Women in Egypt: A Closer Look at Female Genital Mutilation and Intimate Partner Violence; Yasmin Khodary -- 34. Gender based violence in Ghana:experiences of persons with disabilities in two selected areas; Mantey Efua Esaaba, Social Work -- 35. African Diaspora Women Perpetuating Violence Against Men in the United Kingdom; Nomatter Sande -- 36. Adolescent Boys, Young Men and Mental Health in Southern Africa; Mutsawashe Chitando: Public Health, Health Economics Unit and Division -- SECTION G: Preventing Violent Conflict in Africa -- 37. Developing a Framework for Ending Violence in Africa; David Kaulemu, Philosophy -- 38. Confronting dysfunctional military violence in Africa’s electoral spaces: A call for specialised civilian oversight institutions; James Tsabora, Law in the Faculty of Law -- 39. Managing electoral violence through constructive use of social media: Transforming and empowering vulnerable urban youth in Kenya; Joyce W. Gikandi: Christine W. Njuguna, Joan Kabaria- Muriithi, Lucy Kathuri-Ogola -- 40. Managing Conflict in Africa: Challenges and Opportunities for the African Union;Victor H Mlambo: University of Johannesburg School of Public Management, Governance and Public Policy, Ernest Toochi Aniche, Department of Political Science, and Mandla Mfundo Masuku, School of Built Environment and Development Studies -- 41. Through the Afrocentricity Lens: Terror and Insurgency and Implications for Regional Integration in Southern Africa: Reference from Cabo Delgado Province, Mozambique; Daniel N. Mlambo, Tshwane University of Technology -- 42. Insurgency in Mozambique: Incorporating NATO’s Article 5 to the Region’s Quest for Collective Defence;Victor H Mlambo: University of Johannesburg School of Public Management, Governance and Public Policy, and Mfundo Mandla Masuku: School of Built Environment and Development Studies, and Daniel N. Mlambo: Department of Public Management.